The relationship between leader emotional intelligence, team culture and team performance of healthcare institutions in Pakistan / Samia Jamshed - Samia , Jamshed (2018)
The team working in healthcare is figured as a mandatory approach to organizing service delivery and to provide error-free patient care in modern context. Globally, a variety of managerial and clinical teams are found in healthcare setups and among such clinical teams, interdisciplinary teams are the most developed. Therefore, considerable attention is given to the performance of interdisciplinary teams, and studies have linked team performance to satisfactory patient services in healthcare organizations worldwide. Healthcare teams are often ineffective with research showing that 70% of medical errors can be attributed to poor teamwork. Considering the effective team functioning, leader’s non-cognitive abilities and the role of culture remain a central concern of healthcare teams. Therefore, this study seeks to investigate how leader’s emotional intelligence in a prevailing team culture can foster the sharing of knowledge and enhance team emotional intelligence that impacts team performance. The purpose of this research is to consolidate the most robust findings by investigating constructs that influence team performance in private healthcare hospitals of Pakistan where a handful of research was found concerning leader’s emotional intelligence, team culture, and team performance. In order to test the hypotheses; this study employed quantitative approach following the assumptions of positivist paradigm. A survey questionnaire consisting of 67 items reflecting the proposed research constructs were developed for the purpose of primary data collection. By employing cross-sectional study, the data was collected from 195 teams comprised of 735 respondents from 9 private hospitals of Pakistan. For data analysis; study utilized a partial least squares – structural equation modeling approach to validate and confirm the research model by testing the hypothesized relationships. The findings of the study provide empirical evidence of relationships amongst leader emotional intelligence and team culture on team performance. The study findings indicated that leader emotional intelligence has a significant positive relationship with team performance, team emotional intelligence and knowledge sharing. In addition, team culture has a significant positive relationship with team emotional intelligence and knowledge sharing but its relationship with team performance was found to be insignificant. Furthermore, the mediating relationships reveal that the team emotional intelligence and knowledge sharing mediate the relationship between team culture and team performance. By integrating theoretical model, this study contributes to progressing the understanding of leader’s emotional intelligence and team culture in knowledge sharing and enhancing team emotional intelligence. In practice, the study provides valuable inputs for healthcare teams confronting with high work demands where leaders emotional intelligence can create support by understanding emotions of the team and can create a pool of knowledge by sharing with other healthcare professionals. In the end, study implications, limitations, and future research opportunities are emphasized.